2020
DOI: 10.4314/bcse.v34i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ag-Fe3O4 nanoparticles for degradation of methylene blue in aqueous medium

Abstract: Fe3O4 known as magnetite is one of the oxides of iron which plays a major role in various fields of sciences. Fe3O4 was synthesized by precipitation method using NH3.H2O, FeCl2.4H2O and FeCl3.6H2O as precursor materials. For synthesis of 5% Ag-Fe3O4, the green synthetic method was used for immobilization of Ag nanoparticles on Fe3O4 using leaves extract of Calotropis gigantea plant. The synthesized Fe3O4 and 5% Ag-Fe3O4 were employed as catalyst in degradation of methylene blue. The photo catalytic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This loss is due to H 2 O molecules trapped in the crystal structure and moisture in the environment. When the literature is examined, it has been reported that a loss of approximately 8 % in mass after thermal decomposition is normal and that this loss is caused by H 2 O crystals trapped in the structure [41] . It was seen that the synthesis was successful when the results were examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This loss is due to H 2 O molecules trapped in the crystal structure and moisture in the environment. When the literature is examined, it has been reported that a loss of approximately 8 % in mass after thermal decomposition is normal and that this loss is caused by H 2 O crystals trapped in the structure [41] . It was seen that the synthesis was successful when the results were examined.…”
Section: Resultsmentioning
confidence: 99%
“…When the literature is examined, it has been reported that a loss of approximately 8 % in mass after thermal decomposition is normal and that this loss is caused by H 2 O crystals trapped in the structure. [41] It was seen that the synthesis was successful when the results were examined. Likewise, when the TG% graphs of other particles are examined, Fe 3 O 4 @SiO 2 has a 13 % loss by mass, Fe 3 O 4 @SiO 2 À NH 2 has a 15 % loss by mass, Fe 3 O 4 @SiO 2 À Br has a 16 % loss by mass.…”
Section: Characterization Of Particles With Tg-dtamentioning
confidence: 99%
“…Magnetic Iron based nanomaterials include; nano zerovalent Iron Rosická & Šembera, 2011;Vecchia et al, 2009), magnetite (Fe3O4) (Saeed et al, 2020), maghemite (Fe2O3) (Aragaw and Aragaw 2021) and magnetic metal ferrites (Bao et al, 2013). Magnetic iron nanoparticles are widely used in environmental remediation because it is less or non-toxic and sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic iron oxide is a potential photocatalyst for remediation of aqueous contaminants under ultraviolet or visible irradiation because of its outstanding catalytic activities, low production cost, and excellent optical and chemical properties. Despite its unique properties, Fe3O4 has major drawbacks attributed to its wide band gap, which is between 4 -6 eV (Saeed et al, 2020). Recently, researchers have adopted a variety of methods to reduce the wide band gap, quick recombination of electrons, and narrow range of light responses (Su et al, 2021).…”
Section: Introductionmentioning
confidence: 99%